Evaluation of Web Diameter, Flange Thickness, and Adhesive Type on the Physical and Mechanical Properties of Siam Bamboo I-Joist - Lastiur Eva Panggabean; Naresworo Nugroho; Wayan Darmawan; Dede Hermawan; Anggun Thevianni; Khairunnisa Iskandar Putri (Jurnal Ilmu Pertanian Indonesia, 2026)
This study investigates the effect of geometric and adhesive variables on the physical and mechanical properties of I-joist beams using Siam bamboo (Thyrsostachys siamensis) as the web and Acacia mangium as the flange. The research combines two experimental studies focusing on (1) the influence of web diameter (3 cm and 4 cm) and flange thickness (2, 2,5, and 3 cm), and (2) the effect of adhesive type (epoxy and polyurethane) and penetration depth (½, ¾, and full thickness of flange). All materials were conditioned to 12–14% moisture content before fabrication. Physical testing included moisture content and density, while mechanical testing consisted of flexural strength (MOE and MOR), tensile withdrawal strength, and failure mode analysis. Results showed that increasing web diameter and flange thickness contributed to higher density, MOE, and MOR values, with the best performance observed at 3 cm diameter and 3 cm flange thickness. Meanwhile, using epoxy adhesive with ¾ penetration depth significantly improved bonding strength and stiffness, achieving MOE values up to 22,361 kgf/cm² and MOR up to 132 kgf/cm². The most common failure modes were flange cracking and web detachment, particularly in beams with shallow penetration and larger diameters. This combined investigation confirms that optimizing geometric configuration and joint adhesion can significantly enhance the structural performance of bamboo-based I-joists, offering a viable solution for eco-friendly construction. Keywords: bamboo I-joist, web dimension, adhesive, mechanical performance, sustainable construction